Traditional Chinese medicine for HIV-related chronic comorbidities: evidence and potential therapeutic mechanisms - Li, Jiahe; Xu, Liran; Ding, Xue; Ma, Xiuxia; Qian, Pengyu; Qiu, Nao; Yue, Jingyu (Frontiers in Pharmacology, 2026)
HIV-related chronic comorbidities negatively impact health and pose a global public health challenge, necessitating the development of new drugs and therapeutic approaches. Traditional Chinese medicine (TCM) formulations, used for over 2,000 years, are increasingly being studied for the management of these conditions. Recently, an increasing number of studies have investigated the clinical management of HIV-related chronic comorbidities. In this review, we discuss the clinical applications and therapeutic mechanisms of Chinese botanical drugs in treating HIV-related chronic comorbidities, including cardiovascular diseases, chronic kidney disease, neurocognitive disorders, metabolic syndrome, and osteoporosis. We illustrate that various key metabolites, such as tanshinones, berberine, and astragalus polysaccharide, show beneficial effects across these systems, primarily by modulating key pathogenic drivers. The therapeutic mechanisms elucidated primarily involve inhibition of viral replication, modulation of inflammatory pathways (e.g., NF-κB, MAPK, and TLR4), restoration of intestinal mucosal integrity, and rebalancing of immune homeostasis (e.g., Th17/Treg balance). This preclinical evidence supports the effectiveness of these Chinese botanical drugs as complementary and alternative therapeutic options; however, most of the available evidence is based on in vitro and animal studies, and their clinical translational value is significantly limited. Further rigorous clinical trials are needed to verify the efficacy and safety of Chinese botanical drugs in treating people living with HIV.